Understanding how social support influences peer-delivered HIV prevention interventions among Ugandan female sex workers: a case study from HIV self-testing - Maureen McGowan; Stephanie D. Roche; Aidah Nakitende; Jonas Wachinger; Esther Nanyiri; Jocelyn Amongin; Ajiri Nakabuye; Daniel Kibuuka Musoke; Shannon A. McMahon; Till Bӓrnighausen; Katrina F. Ortblad (BMC, 2022)
Abstract Background Female sex workers (FSWs) have tightly connected peer networks and remain at high risk of HIV acquisition. Peer delivery of HIV prevention interventions, such as HIV self-testing (HIVST), is a recommended implementation strategy for increasing intervention uptake and continuation among FSWs. We analyzed qualitative data from a peer-delivered HIVST intervention among FSWs in urban Uganda to understand the ways social support within this peer network can motivate or discourage the uptake of peer-delivered HIVST. Methods Between February and April 2017, we conducted in-depth interviews (IDIs) with FSWs (n = 30) and focus group discussions (FGDs) with FSW peer educators (PEs, n = 5) finishing participation in a four-month randomized implementation trial testing models of peer-delivered HIVST in Kampala. FSW participants were ≥ 18 years old, self-reported exchanging sex for money or goods (past month) and had not recently tested for HIV (past 3 months). FSW PEs either directly distributed HIVST kits to participants or provided coupons exchangeable for HIVST kits from specified healthcare facilities. In the IDIs and FGDs, we asked participants to share their experiences receiving or delivering peer-delivered HIVST, respectively. Using a hybrid deductive and inductive coding approach, we arranged findings along the dimensions of an established social support theory: informational, instrumental, and emotional support. Results The median age of participants was 30 years (IQR: 27-33) and PEs was 33 years (IQR: 29-37). We found that social support within FSW peer networks both motivated and discouraged uptake of peer-delivered HIVST. For example, sharing positive HIVST experiences (informational support), directly delivering HIVST kits (instrumental support), and encouraging linkage to care (emotional support) motivated HIVST uptake among FSWs. Conversely, the spread of misinformation (informational support), limited HIVST kit availability fostering mistrust of PEs (instrumental support), and fear of social exclusion following HIV status disclosure (emotional support) discouraged HIVST uptake among FSWs. Conclusions In Uganda, social support (e.g., informational, instrumental, and emotional support) among FSW peers can work in ways that both motivate and discourage peer-delivered intervention uptake. Future FSW peer-delivered HIV prevention interventions should be designed around the dimensions of social support within FSW peer networks to maximize initial and repeat intervention delivery and uptake.